PERMEATION OF BENTONITE SUSPENSIONS THROUGH LOOSE SANDY SOIL (Malaysian Journal of Civil Engineering, 2018)
Over the past years, the levee breach flood disaster caused by underseepage has become an alarming problem in Bangladesh. The underseepage phenomenon beneath the earthen embankments may be controlled by treating the underlying granular soil with grout suspensions delivered by permeation (permeation grouting), resulting in a less permeable deposit. Drawing on this physical link, a permeameter was fabricated to investigate the permeation of bentonite suspension through the granular soil medium. The variation of injection time of stopping grout flow, injected grout weight, penetration distance with bentonite fraction for a constant pressure grout injection were studied. The time dependent effluent flow rate variation were also monitored in the laboratory. The experimental results showed that grouting operation worked efficiently for a certain range of bentonite fraction. The individual parameters like injection time, penetration distance, injected grout weight decreased with the increase of bentonite concentration. The effluent flow rate reduction became much prominent as the test proceeded towards the end that justified the effectiveness of permeation. Finally, a grout concentration was proposed considering the cost and other factors like penetration distance, injection time etc. for the sand used in this investigation.